2020
DOI: 10.3390/jcm9010149
|View full text |Cite
|
Sign up to set email alerts
|

Admission Hyperglycemia as a Predictor of Mortality in Acute Heart Failure: Comparison between the Diabetics and Non-Diabetics

Abstract: Background: To investigate the impact of admission hyperglycemia (HGL) on in-hospital death (IHD) and 1-year mortality in acute heart failure (AHF) patients with or without diabetes mellitus (DM). Methods: Among 5625 AHF patients enrolled in a nationwide registry, 5541 patients were divided into four groups based on the presence of admission HGL and diabetes mellitus (DM). Admission HGL was defined as admission glucose level > 200 mg/dL. IHD and 1-year mortality were compared. Results: IHD developed in 269 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(20 citation statements)
references
References 27 publications
2
17
0
1
Order By: Relevance
“…16 Previous studies defined normoglycaemia as no previous history of DM and HbA1c < 6.4% or 6.5%. 13 , 17 Previous report demonstrated that the ethnic differences in the relationship between insulin sensitivity and insulin response and the genetic background of East Asians are susceptible to diabetes than Caucasians. 18 That is the reason why abnormal glucose metabolism is likely to occur even if the value of HbA1c is normally high in East Asians.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…16 Previous studies defined normoglycaemia as no previous history of DM and HbA1c < 6.4% or 6.5%. 13 , 17 Previous report demonstrated that the ethnic differences in the relationship between insulin sensitivity and insulin response and the genetic background of East Asians are susceptible to diabetes than Caucasians. 18 That is the reason why abnormal glucose metabolism is likely to occur even if the value of HbA1c is normally high in East Asians.…”
Section: Methodsmentioning
confidence: 99%
“… 10 , 11 , 12 In nondiabetic patients with acute heart failure, admission hyperglycaemia was an independent predictor of one‐year mortality, despite diabetes mellitus (DM) itself not carrying this prognosis. 13 The association between admission hyperglycaemia and clinical outcome in nondiabetic HFpEF patients has not been elucidated.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, both diabetes and hyperglycemia directly in uence atherosclerotic plaque formation and progression and may induce microvascular dysfunction and microangiopathy. Therefore, the resulting vicious circle might affect the macrovascular and microvascular beds, leading to an adverse long-term prognosis in both MIOCA and MINOCA patients [33][34][35] .…”
Section: Hyperglycemia and Long-termoutcomesmentioning
confidence: 99%
“…T2D is closely associated with those 2 phenotypes of cardiomyopathy in humans [ 18 ]. Recent studies have shown that poor glycemic control correlates with increased risk of HF in diabetic patients, and the myocardial changes in those patients are believed to be induced by hyperglycemia [ 19 , 20 ]. T2D was known to be one of the main risk factors and determinants of HFrEF.…”
Section: Introductionmentioning
confidence: 99%